Hyptidendron albidum (Lamiaceae, Hyptidinae), a remarkable new species from northern Minas Gerais state, Brazil - Harley, Raymond Mervyn; Antar, Guilherme Medeiros (Phytotaxa, 2017)
Hyptidendron albidum a new and endemic species from Northern Minas Gerais state, Brazil, is here described. This new species is unique due to the morphological combination of its dense indumentum of white dendroid trichomes, covering much of the plant and the inflorescence composed of a unilateral cymose structure. The new species is morphologically similar to H. unilaterale which displays a similar unilateral cymose structure but differs in its indumentum, inflorescence length and leaf morphology. We provide a description, an illustration, a conservation status assessment, a distribution map, and comments on the recognition of this new species.